2012
DOI: 10.1111/j.1742-9544.2011.00044.x
|View full text |Cite
|
Sign up to set email alerts
|

Professional Training in Applied Psychology: Towards a Signature Pedagogy for Forensic Psychology Training

Abstract: Forensic Psychology is a recognised and important sub-specialty of the Psychology discipline. However, after an expansion in the number of training places that were offered when programmes were first developed, recent years have seen these diminish in response to changes in university policies, resulting from reformulated Federal government funding models. In this article, we argue that it is important for the future of specialist areas of professional psychology to not only articulate the core skills and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In addition to the reviewed articles featured here, other articles were identified that are not included in the review because they did not fit the inclusion criteria, but nonetheless are worth noting for their relevance to the broader aims of this paper. They relate to potential of PBL for clinical psychology (Baillie et al, 2011;Huey, 2000), educational psychology (Dunsmuir & Frederickson, 2014;Jordan & Porath, 2006) and forensic psychology (Day & Tytler, 2012). There were also articles that drew on the use of PBL in psychology courses for primarily research purposes, notably Dahlgren and Dahlgren (2002) and Dahlgren (2003) (Linko¨ping University, Sweden), de Koning et al (2014;Erasmus University Rotterdam, Netherlands ), Van den Hurk (2006; Maastricht University, Netherlands), Wijnia et al (2014;Erasmus University Rotterdam, Netherlands) and also Contreras, Rodriguez-Espartal, Augusto Landa, and Lopez-Zafra (2013; University of Jaen, Spain).…”
Section: Child and Adolescentmentioning
confidence: 99%
“…In addition to the reviewed articles featured here, other articles were identified that are not included in the review because they did not fit the inclusion criteria, but nonetheless are worth noting for their relevance to the broader aims of this paper. They relate to potential of PBL for clinical psychology (Baillie et al, 2011;Huey, 2000), educational psychology (Dunsmuir & Frederickson, 2014;Jordan & Porath, 2006) and forensic psychology (Day & Tytler, 2012). There were also articles that drew on the use of PBL in psychology courses for primarily research purposes, notably Dahlgren and Dahlgren (2002) and Dahlgren (2003) (Linko¨ping University, Sweden), de Koning et al (2014;Erasmus University Rotterdam, Netherlands ), Van den Hurk (2006; Maastricht University, Netherlands), Wijnia et al (2014;Erasmus University Rotterdam, Netherlands) and also Contreras, Rodriguez-Espartal, Augusto Landa, and Lopez-Zafra (2013; University of Jaen, Spain).…”
Section: Child and Adolescentmentioning
confidence: 99%
“…Over 100 years ago, the responsibility for training those within practice-based disciplines was moved from an apprentice-style model to higher education (Day & Tytler, 2012). Prior to this, it was typical for students within professional practice programs to learn by doing (i.e., situated in the field as opposed to in a classroom).…”
Section: Literature Review Higher Education Professional Practice Pro...mentioning
confidence: 99%
“…Work readiness skills predict job performance, career advancement, and even potential for promotion, all of which are context (discipline) specific ( Gardner and Liu, 1997 ; Crebert et al, 2004 ; Hart, 2008 ). Finally, work readiness helps shape graduates’ professional identity, which is a concept that manifests differently across disciplines and career pathways ( Hind et al, 2003 ; Day and Tytler, 2012 ; Winterton and Tuner, 2019 ). As such, discipline specific research into work readiness may assist graduate outcomes.…”
Section: Introductionmentioning
confidence: 99%